Continuous market growth beyond functional satiation: time-series analyses of US footwear consumption, 1955-2002 - Alexander Frenzel Baudisch (Max Planck Institute of Economics, 2006)
Market growth is driven by product innovation. Beyond functional satiation the marginal utility of product performance and variety decreases. We argue that social comparisons underlying innovation diffusion results in consumer motivations for upward assimilation toward the behavior of better performing others, even beyond functional requirements. We distinguish consumption growth patterns driven by functional vs. assimilating motivations. These patterns are tested by time-series analyses of U.S. Footwear consumption between 1955 and 2002. The acceleration of market growth since the 1970s is statistically explained by changes in price, cross-price elasticity, and the increasing demand for innovations, according to our theoretical account of consumption motivations beyond functional satiation.
Keywords: C22; D01; D12; L67; O33; 330; Product Innovation; Innovation Diffusion; Consumption Growth; Social Comparison; Time-Series Analysis